PENGARUH STATUS SOSIAL EKONOMI ORANG TUA TERHADAP MINAT BERWIRAUSAHA MAHASISWA TEKNIK SIPIL - Khairul Umam; Dr. Nurhasan Syah, M.Pd (Universitas Negeri Padang, 2019)
Abstract— This study aims to find out the influence of social-economy status of a parent toward the entrepreneurship interest of Civil Engineering students. This research applies Descriptive quantitative method with a total population of 77 students of Civil Engineering and Building 2017, FT UNP. The technique of sampling the data by using Proporsive Random Sampling with 47 persons of the total sample. The technique of collecting the data by using a questionnaire method. Before conducting research on 47students, the research trial is conducted with 30 students of Civil Engineering and Building 2017, FT UNP. The trial aims to find out whether the instrument use is valid and reliable. The processing data in this research by using the SPSS 16.00program. The result of this study indicates that there is no influence between the last education and income of a parent towards the interest in entrepreneurship in Civil Engineering and Building students of 2017. Keywords: Parent’s last education, parent’s income, interest in entrepreneurship, Civil Engineering and Building 2017.